Pengaruh Teknik Pengendalian Gulma dan Frekuensi Aplikasi Insektisida terhadap Kelimpahan Populasi dan Intensitas Serangan Hama Utama pada Tanaman Lada (Piper nigrum L.): Pengaruh Teknik Pengendalian Gulma dan Frekuensi Aplikasi Insektisida Terhadap Kelimpahan Populasi dan Intensitas Serangan Hama Utama pada Tanaman Lada (Piper nigrum L.) - Rion Apriyadi; Tri Lestari (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2021)
The control of pepper stem borer Lophobaris piperis Marsh (Coleoptera: Curculionidae) and berry sucker Dasynus piperis China (Hemiptera: Coreidae) is using insecticide application and culture technique. The objectives of the research was to asses the effect of weed control techniques and the frequency of insecticide application to the abundance and damage intensity caused by L. piperis and D. piperis on pepper plant. The research was conducted in local farmer pepper plantation with combination of weed control technique (weeding, herbicide, and Arachis pintoi) and frequency of insecticide application (2 and 4 times a year). The abundance of pepper plant pests has discovered in pepper plantation with weed control using weeding and herbicide application combined with frequency of insecticide application 4 times a year. The highest absolute damage intensity and relative damage intensity were found in pepper plantations with a frequency of insecticide applications 2 times a year. The damage intensity tended to decrease in pepper plantation that applied weed control techniques using A. pintoi.